Teacher’s Delivery Format and ADDIE Model to Adjust the Online Learning System during the Pandemic Period - Kartika Hajati; Nur Amaliah (Universitas Jambi, Indonesia, 2022)
The type of the research is research and development by using the ADDIE model. The ADDIE model of instructional design is a generic instructional model that provides an organized process for developing instructional materials. This systemic model is a five-step cyclical process that can be used for both traditional and online instruction. The five steps are analyzing, designing, developing, implementing, and evaluating. The sample of the research were 36 students of Biology study program at one public university in Sulawesi Barat. The learning tools developed consist of semester learning plan (RPS), lecture contracts, learning media, and evaluation instruments. The research found that the validity of the learning device was 90.4% and in the very valid category with minor revisions. Then, the practicality of learning devices based on the implementation of RPS and observation results was 94% which indicates a very practical category to use. The effectiveness of learning devices based on student learning test results was 80.45% which indicates an effective category. Thus, the results of this research were valid, practical, and effective.